2020
DOI: 10.1108/lhs-07-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ voice: the role of hierarchy and leadership

Abstract: Purpose Voicing concerns and suggestions is crucial for preventing medical errors and improving patient safety. Research suggests that hierarchy in health-care teams impair open communication. Hierarchy, however, can vary with changing team composition, particularly during acute care situations where more senior persons join the team later on. The purpose of this study is to investigate how changes in hierarchy and leadership were associated with nurses’ voice frequency and nurses’ time to voice during simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…These approaches have led to the insight that safety voice can be promoted (in terms of likelihood or onset) through leaders acting in low power distance ways. For instance, through providing encouragements, using inclusive language (Barzallo Salazar et al, 2014;Weiss et al, 2018) or shallower hierarchies (Krenz et al, 2020). Furthermore, this research indicated that risk perceptions are necessary for successful interventions (Noort et al, 2019b), and that safety voice emerges after a decision on the trade-off between the benefit of mitigating harm and the cost of leaders' poor safety listening (Schwappach and Gehring, 2014a).…”
Section: Safety Voice For Safety-critical Staffmentioning
confidence: 84%
See 3 more Smart Citations
“…These approaches have led to the insight that safety voice can be promoted (in terms of likelihood or onset) through leaders acting in low power distance ways. For instance, through providing encouragements, using inclusive language (Barzallo Salazar et al, 2014;Weiss et al, 2018) or shallower hierarchies (Krenz et al, 2020). Furthermore, this research indicated that risk perceptions are necessary for successful interventions (Noort et al, 2019b), and that safety voice emerges after a decision on the trade-off between the benefit of mitigating harm and the cost of leaders' poor safety listening (Schwappach and Gehring, 2014a).…”
Section: Safety Voice For Safety-critical Staffmentioning
confidence: 84%
“…Yet, crucially, these methods assume generalisability to actual accidents, and insights on the extent to which, and how precisely, safety voice and safety listening contribute to real accidents remain scare and limited (Krenz et al, 2020;Noort et al, 2019b;Peadon et al, 2019). Moreover, the role of power distance for safety voice during naturally occurring scenarios remains an assumption.…”
Section: Safety Voice For Safety-critical Staffmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy between how people think they would behave and how they actually behave is particularly noticeable when it comes to potentially threatening and embarrassing issues, which are prevalent in many voice situations (Argyris 1980). Thus, if research relied solely on self-report data, there would be still a lack of insight regarding when, whether, and how people show voice (Krenz et al 2020).…”
Section: Measurements Of Voicementioning
confidence: 99%